A Origem do Paradigma Desenvolvimentista de Interpretação dos Diálogos de Platão - Matoso, Renato (Revista Archai, 2016)
The fact that Plato adopted a literary form of writing presents a great number of challenges to the reader interested in his philosophy. The greatest of these challenges follows from the fact that Plato himself is not one of his characters. If we could find Plato among the characters of his dialogues, it would be easy for us to identify his positions. However, Plato’s absence of the dramatic scenes he depicted leaves us without an easy solution for this fundamental problem: how to access Plato’s positons and thought about the many themes debated in the dialogues? Throughout history, different methods of reading and organizing Plato’s work were developed in order to deal with this problem and to give to the reader of the dialogues an access to Plato’s thoughts and positions. This paper aims to present an assessment of the development of the latest, and still widely adopted, paradigm of reading Plato’s work. Through the analysis of the major commentators responsible for the establishmentnof the current paradigm of organization and reading of Plato’s dialogues, the paper aims to reflect on the qualities, vices, and prejudices inherent to our way of reading Plato. Keywords: Plato, Dialogues, Chronology.